2023
DOI: 10.1128/mbio.03073-22
|View full text |Cite
|
Sign up to set email alerts
|

Depleting Cationic Lipids Involved in Antimicrobial Resistance Drives Adaptive Lipid Remodeling in Enterococcus faecalis

Abstract: The cell membrane plays a pivotal role in protecting bacteria against external threats, such as antibiotics. Cationic phospholipids such as lysyl-phosphatidyglycerol (L-PG) resist the action of cationic antimicrobial peptides through electrostatic repulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…It is also important to note that while this study focuses on This is especially relevant since the ΔmprF1 ΔmprF2 strain is known to possess a drastically altered lipidome, which could hint to possible alterations in membrane microdomain organization and consequent protein localization (Rashid et al, 2023). Membrane microdomains are domains of different lipid composition within the cell membrane where cellular processes are organized (Barák & Muchová, 2013;Lopez & Koch, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also important to note that while this study focuses on This is especially relevant since the ΔmprF1 ΔmprF2 strain is known to possess a drastically altered lipidome, which could hint to possible alterations in membrane microdomain organization and consequent protein localization (Rashid et al, 2023). Membrane microdomains are domains of different lipid composition within the cell membrane where cellular processes are organized (Barák & Muchová, 2013;Lopez & Koch, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple peptide resistance factor mutations have not been reported in association with enterococcal DAP R . While there is only one mprF gene in the S. aureus genome, E. faecalis and E. faecium encode two paralogs—MprF1 and MprF2—where MprF2 appears to be the major contributor to PG aminoacylation in E. faecalis (Bao et al., 2012; Rashid et al., 2023). We have also reported that mprF is closely tied to global lipidome regulation and cell physiology, and the absence of mprF significantly alters membrane lipid composition resulting in altered membrane fluidity, reduced secretion, and increased dependence on exogenous fatty acids (Rashid et al., 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…E. coli mutants lacking PG and CL in the membrane are still viable at temperatures less than 40 °C33 and the functions of PG in a E. faecalis mutant with reduced membrane PG can be compensated by diglucosyl-diacylglycerol lipids. 34 CLs are synthesised through the condensation of two molecules of PG by cardiolipin synthases ClsA/B and transfer of a phosphatidyl moiety from PE to PG by ClsC in E. coli, while a stress inducible cls1 and constitutive cls2 genes are expressed in S. aureus for CL synthesis. 21 The formation of distinct domains rich in CLs at cell poles and septa are critical during cell division.…”
Section: The Main Classes Of Membrane Lipidsmentioning
confidence: 99%
“…Since ∆mprF mutants originally identified in S. aureus were susceptible to multiple AMPs due to the lack of Lys-PG, the gene was named multiple peptide resistance factor [52]. After that, deficiency in Lys-PG synthesis in ∆mprF mutants was linked to cationic AMP susceptibility in several other bacteria, including Bacillus anthracis, B. subtilis, Enterococcus faecalis, Listeria monocytogenes, Mycobacterium tuberculosis, and Pseudomonas aeruginosa [53][54][55][56][57][58][59]. MprF proteins proved to be crucial for the virulence of various pathogens, thereby demonstrating an essential role of MprF in bacterial immune evasion and making it an attractive target for the development of antivirulence strategies [60].…”
Section: Introductionmentioning
confidence: 99%